Fluvastatin inhibits cardiomyocyte apoptosis after myocardial infarction through Toll pathway - Jia, Lili (Exp Ther Med, 2018)
The present study intended to investigate the effect of fluvastatin on cardiomyocyte apoptosis after myocardial infarction in rats. Eighty myocardial infarction rat models were established and randomly divided into 4 groups (n=20): experimental group (n=20) was given fluvastatin treatment; sham operation group (n=20) and normal control group (n=20) were given saline. The dose of fluvastatin was 20 mg/(kg·d), and irrigation gavage was given for 1 week. Western blot analysis and reverse transcription-quantitative PCR (RT-qPCR) were used to detect the expression of TLR4 mRNA and protein in cardiomyocytes. TUNEL method was used to detect the apoptosis of cardiomyocytes. After fluvastatin treatment for 1 week, RT-qPCR found that compared with myocardial infarction group, the TLR4 mRNA expression of fluvastatin treatment group and normal control group was significantly increased, and the differences between groups were a statistically significant difference (P<0.05). Western blot analysis showed that compared with the myocardial infarction group, the expression of TLR4 protein in normal control group, sham operation group and fluvastatin treatment group were significantly decreased, and they all were statistically significant (P<0.05). TUNEL method found that compared with the myocardial infarction group, the fluvastatin treatment group could significantly reduce the apoptosis of cardiomyocytes (19.2±3.8%), and the difference was statistically significant (P<0.05). Fluvastatin can inhibit myocardial infarction and decrease cardiomyocyte apoptosis by increasing the expression of TLR4-like receptor.